Fabrication and characterization of high order filter based on resonance in hybrid multi-knots microfiber structure - Nodehi, S.; Mohammed, W.S.; Ahmad, Harith; Harun, Sulaiman Wadi (Elsevier, 2016)
This work proposes a novel design of a hybrid microfiber resonator which can be used as a band-pass and band-stop filter in various applications such as fiber lasers. The structure comprises of two microfiber knot resonators with different sizes which are surrounded by a semi-loop structure with one input and two output ports. Utilization of the Vernier effect in the proposed structure showed an enhancement of the free spectral range (FSR). The finesse has increased by a factor of three compared to a single knot providing a sharper roll-off. The filter bandwidth is adjustable as a result of the manipulation of the coupling length and rings' radii. The performance of the device is explained theoretically using transfer matrix analysis.